The Impact of EDTA and Sodium Hexametaphosphate Habit Modifiers in the Production of Quality Soda Ash Crystals - S. Raditladi, Zukiswa; C. Ngila, Jane; V. Kgarebe, Boitumelo; Ddamba, W. (Asian Journal of Chemistry, 2016)
The impact of two sequestering agents, namely, ethylenediaminetetraacetic acid (EDTA) and sodium hexametaphosphate (SHMP) on the morphology, size and purity of soda ash was studied. Analysis of soda ash crystals, precipitated by bubbling carbon dioxide through the brine solution, was done using various techniques including powder X-ray diffraction (XRD), differential thermal analyse/thermogravimetric analyses (DTA/TGA), environmental scanning electron microscope (ESEM) and ion chromatography (IC). Crystals produced in the presence of SHMP resulted in spherical shapes which is a more desirable morphology compared to the needle-like shapes observed for the control sample. On the other hand, the presence of EDTA maintained the undesirable needle-like shapes. Each sequestering agent had an optimum concentration (EDTA = 1.09 × 10–2% w/v and SHMP = 2.13 × 10–2–2.17 × 10–2% w/v) that gave the best product purity as demonstrated by minimum impurities in the final product. The particle size distribution (PSD) results show that the soda ash grown in the presence of SHMP had the largest particle sizes ranging between 180 and 500 microns while that of both the control and EDTA samples had particle sizes between 0 and 180 microns.